Kebijakan Pengelolaan Sampah Bernilai Ekonomi di Desa Tanjung Atap Barat Ogan Ilir - Nur Husni Emilson; Reny Okpirianty; Helwan Kasra; Dea Justicia Ardha; Gumar Herudiansyah; Febrina Hertika Rani; Sarah Qosim (Universitas Muhammadiyah Yogyakarta, 2023)
This activity addressed waste problems in Tanjung Atap Barat Village, Ogan Ilir Regency. The community has tried to deal with it, but it has not been optimal. Another reason is to increase public awareness of waste management so it becomes a medium to improve the economy and create a society’s legal awareness. Thus, what is village regulations' role in waste management in Tanjung Atap Barat village? What steps can be taken so that the waste problem in Tanjung Atap Barat village becomes of economic value? By following the Regulation of Tanjung Atap Barat Village Number 003 of 2020 About the Management of Household Waste and the Surrounding Environment, the community improves waste management in the village and raises awareness of environmental issues. Village Regulation Number 003 of 2020 has a system consisting of 14 chapters and 37 articles. If it is examined more deeply, waste has the potential to affect household income. Therefore, improvement can start through its citizens, especially women and the younger generation. Every household is involved in managing at least its own waste, socialization, training, mentoring, and direct practice to increase public understanding and knowledge in handling waste into economic value. Especially in Tanjung Atap Barat village, it has started with placing trash cans in every house. Also, waste is segregated by its type: plastic, paper, and household waste.